2020
DOI: 10.5194/se-11-2327-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of upper mantle convection on lithosphere hyperextension and subsequent horizontally forced subduction initiation

Abstract: Abstract. Many plate tectonic processes, such as subduction initiation, are embedded in long-term (>100 Myr) geodynamic cycles often involving subsequent phases of extension, cooling without plate deformation and convergence. However, the impact of upper mantle convection on lithosphere dynamics during such long-term cycles is still poorly understood. We have designed two-dimensional upper-mantle-scale (down to a depth of 660 km) thermo-mechanical numerical models of coupled lithosphere–mantle deformation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 106 publications
4
33
0
Order By: Relevance
“…(A9). Previous work has demonstrated that this choice, in combination with suitable flow law parameters, results in a viscosity structure that is consistent with geophysical constraints with respect to the convection dynamics of the mantle and the thermal thickness of the overlying, horizontal lithosphere (Candioti et al, 2020). Similar average grain sizes of the order of 1 mm in the upper mantle have been predicted by whole mantle convection models that include state-of-the-art grain size evolution models (Dannberg et al, 2017;Schierjott et al, 2020).…”
Section: Model Configurationsupporting
confidence: 62%
See 3 more Smart Citations
“…(A9). Previous work has demonstrated that this choice, in combination with suitable flow law parameters, results in a viscosity structure that is consistent with geophysical constraints with respect to the convection dynamics of the mantle and the thermal thickness of the overlying, horizontal lithosphere (Candioti et al, 2020). Similar average grain sizes of the order of 1 mm in the upper mantle have been predicted by whole mantle convection models that include state-of-the-art grain size evolution models (Dannberg et al, 2017;Schierjott et al, 2020).…”
Section: Model Configurationsupporting
confidence: 62%
“…However, thermal softening, caused by shear heating, is active, resulting from the conservation of energy and temperature-dependent viscous flow stress. The algorithm has already been used to model deformation processes at various scales (Yamato et al, 2015;Duretz et al, 2016b;Yamato et al, 2019;Petri et al, 2019;Bessat et al, 2020) including upper mantle convection coupled to lithospheric-scale defor-L. G. Candioti et al: Buoyancy versus shear forces in building orogenic wedges mation (Candioti et al, 2020). Appendix A provides a detailed description of the algorithm.…”
Section: Mathematical Model and Numerical Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments with dry dislocation creep result in extensive brittle-plastic deformation of the lithosphere 43,44 . Experiments with composite diffusion-dislocation creep and small constant grain size (1 mm) results in a lithosphere thinned by convective erosion (<90 km) driven by low asthenosphere viscosities of <10 18 Pa•s 16,45 . For constant grain sizes larger than 1 cm, dislocation creep becomes the main deformation mechanism throughout the entire upper manlte 16 .…”
Section: Effects Of Grain Size On Lithospheric Strengthmentioning
confidence: 99%